Pulsed laser amplification in master oscillator : power amplifier (MOPA) configuration - Seah, Ee Seng. (2009)
This report is focused on the establishment of Pulsed Laser Amplification in a Master Oscillator Power Amplifier (MOPA) and discussion of the various methods of achieving such a system. By examining our approaches, we desired to enhance our knowledge in fiber laser technologies.